Prove It MHF Helper Aug 2008 12,897 5,001 Sep 2, 2012 #2 graham1664 said: p^2-16(q-r)^2 (Wink) Click to expand... First of all, that's an expression, NOT an equation. Second, it's a Difference Of Two Squares.

graham1664 said: p^2-16(q-r)^2 (Wink) Click to expand... First of all, that's an expression, NOT an equation. Second, it's a Difference Of Two Squares.

A AbigailEMG Sep 2012 1 0 United Kingdom Sep 4, 2012 #3 p^2 - 16(q-r)^2 = (p – 4(q - r))(p + 4(q - r)) as x^2 = p^2 and a^2 = 16(q-r)^2 p^2 - 16(q-r)^2 = (p – 4q + 4r)(p + 4q - 4r)

p^2 - 16(q-r)^2 = (p – 4(q - r))(p + 4(q - r)) as x^2 = p^2 and a^2 = 16(q-r)^2 p^2 - 16(q-r)^2 = (p – 4q + 4r)(p + 4q - 4r)